Developing Physics-Integrated Computational Thinking Skills Assessment Instrument Using Rasch Measurement Model (Jurnal Pendidikan Fisika dan Keilmuan (JPFK), 2023)
Computational thinking skills (CT) are an essential skill for young generations. Integration of CT in physics has been studied widely since they are closely related to each other. However, instruments to assess CT in physics problem-solving are still limited. This study aims to develop a physics-integrated CT assessment instrument. Multiple choice items were developed and reviewed by experts in physics education. A pilot study is conducted with 121 undergraduate students. Based on the empirical data on the pilot study, the Rasch analysis using Winstep is conducted. The final instrument consists of 24 multiple-choice items. Each item has MNSQ in the range of 0.82-1.17. The ZSTD is in the range of -1.92-1.99 which can be classified in fit. Calculation with the Rasch model for 24 fit items shows person reliability of 0.81, item reliability of 0.89, and alpha Cronbach of 0.89. Those values can be classified as good.